Mycobacterium fortuitum and Mycobacterium abscessus infections in the foot and ankle in two immunocompetent patients - Wong, Khai Phang (Biomedicine (Taipei), 2020)
Nontuberculous mycobacteria (NTM) infections of the musculoskeletal system are commonly missed due to its rarity and the absence of systemic symptoms. A high clinical index of suspicion is required to recognize such infections as they may occur in immunocompetent hosts. We present two cases of foot and ankle NTM infections involving Mycobacterium fortuitum and Mycobacterium abscessus in two such patients. The first case involves an 83-year old lady who presented with a two-month history of multiple foot abscesses initially treated at a rural hospital. She underwent drainage and debridement of her foot, with eventual cultures growing Pseudomonas aeruginosa and Mycobacterium abscessus. She was initially treated with clarithromycin and doxycycline. At one year follow-up review, her wound healed completely. The second case involves a 55-year old man who presented with infection following midfoot fusion and anterolateral thigh flap for an open complex fracture dislocation of his right foot. Cultures eventually grew Mycobacterium fortuitum and he was treated with cefoxitin, clarithromycin and doxycycline. 10 months after his initial injury, the infection has cleared and his flap was clean. Through these 2 cases, we hope to highlight the unusual presentations of such infections and illustrate that with a high initial index of suspicion and appropriate treatment, these infections can be treated successfully.